Continuous Support Promotes Obstetric Labor Progress and Vaginal Delivery in Primiparous Women – A Randomized Controlled Study - Stjernholm, Ylva Vladic; Charvalho, Paula da Silva; Bergdahl, Olga; Vladic, Tomislav; Petersson, Maria (Frontiers in Psychology, 2021)
Background Obstetric labor and childbirth are mostly regarded as a physiological process, whereas social, cultural, psychological and transcendental aspects have received less attention. Labor support has been suggested to promote labor progress. The aim of this study was to investigate whether continuous labor support by a midwife promotes labor progress and vaginal delivery. Material and methods A randomized controlled study at a university hospital in Sweden in 2015−17. Primiparous women with singleton pregnancy and spontaneous labor onset were randomised to continuous support (n = 30) or standard care (n = 29) during delivery. The primary outcome was the duration of active labor. Secondary outcomes were delivery mode, women´s need of labor analgesia and satisfaction with delivery, maternal cortisol levels and neonatal morbidity. Results Continuous support was followed by shorter active labor 11.0 ± 5.7 hours compared to 13.7 ± 3.9 hours with standard care (p = 0.001). Women in the continuous support group tended to have lower cortisol levels and low cortisol during the first (p = 0.02) and second (p = 0.04) stages of labor were correlated with shorter active labor. Continuous support was followed by spontaneous delivery in 73%, instrumental delivery in 24% and emergency cesarean section in 3% in contrast to standard care which was followed by spontaneous delivery in 62%, instrumental delivery in 24% and cesarean in 14% (p = 0.19). The continuous support group received combined analgesic methods more often (p = 0.04). Women´s satisfaction with delivery and neonatal morbidity were comparable. Conclusion Continuous labor support was followed by shorter active labor compared to standard care. Women with continuous support had a high rate of vaginal delivery and tended to have lower cortisol levels during all stages of active labor reflecting a lower stress level. Low cortisol was correlated to shorter active labor. Based on these results, we recommend continuous labor support for all primiparous women during active labor.